2005
DOI: 10.1002/bjs.5000
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of technique for closure of the pancreatic remnant after distal pancreatectomy

Abstract: The quality and quantity of information extracted from the available trials are insufficient to enable any firm conclusion to be drawn on the optimal surgical technique of pancreatic stump closure; there is a trend in favour of the stapling technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
259
1
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(277 citation statements)
references
References 32 publications
7
259
1
10
Order By: Relevance
“…[4,19] Further studies have shown that closure with a stapler had a more favorable effect than conventional hand sewn closure. [3,20] In a systematic review, the use of stapler closure in DP significantly reduces POPF rates compared with suture closure. The combination of stapler and suture was found to be superior over suture alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,19] Further studies have shown that closure with a stapler had a more favorable effect than conventional hand sewn closure. [3,20] In a systematic review, the use of stapler closure in DP significantly reduces POPF rates compared with suture closure. The combination of stapler and suture was found to be superior over suture alone.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Although these are encouraging results, postoperative pancreatic fistula (POPF) still occurs at 24% to 39%. [2][3][4][5] In previous studies, the suggested risk factors of POPF after DP were body mass index (BMI), [6] pancreatic thickness, [7] and pancreatic texture. [8] Among these risk factors, thickness is an adjustable factor influenced by the stapler.…”
Section: Introductionmentioning
confidence: 99%
“…No method has proven superior for preventing postoperative fistulas or leaks. 19,20 Preservation of the pancreatic tail must be attempted in patients with injury to the right of the mesenteric vessels, where complete resection can lead to endocrine compromise in up to 50% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…O fechamento por pontos, a utilização de grampeadores, a utilização de "patch" seroso e mesmo a anastomose pancreática, são possibilidades técnicas. Knaebel et al 19 , a partir de 262 publicações, selecionaram 10 estudos para a revisão sistemática e seis para a metanálise na avaliação da melhor técnica de tratamento do coto pancreático pós-pancreatectomia corpo-caudal. A maioria das publicações utilizadas na revisão sistemática foi baseada em estudos observacionais com amostragem insuficiente, viés de seleção e definições não homogêneas de fístula pancreática, tornando conclusão inadequada sobre o assunto.…”
Section: Tratamento Do Coto Pancreáticounclassified
“…A maioria das publicações utilizadas na revisão sistemática foi baseada em estudos observacionais com amostragem insuficiente, viés de seleção e definições não homogêneas de fístula pancreática, tornando conclusão inadequada sobre o assunto. A despeito disso, a metanálise apontou para uma tendência de menor incidência de fístula com o grampeamento 19 . Esse dado é discordante com estudo recente, prospectivo, não randomizado, com 302 pacientes consecutivos submetidos à pancreatectomia corpo-caudal no qual o fechamento do coto pancreático por meio de grampeador foi associado com significante maior índice de fístula pancreática 17 .…”
Section: Tratamento Do Coto Pancreáticounclassified